1995
DOI: 10.1111/j.1365-2095.1995.tb00042.x
|View full text |Cite
|
Sign up to set email alerts
|

Energy budget and metabolism in common carp, Cyprinus carpio L., fed on different dietary protein levels and at different ration levels

Abstract: The total energy budget of 65 k 8.0 g common carp, Cyprinus carpio L., was studied in the laboratory. The pattern of energy allocation varied with dietary protein content and ration levels. The energy lost as heat of metabolism, R, was found to increase with dietary protein level and total ration. Energy lost as faeces, F, varied from 19% to 24% of consumption, C, but did not appear to be related to either protein content or ration levels. The energy equivalent of nitrogenous excretion, U, as a proportion of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

2006
2006
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
2
6
0
Order By: Relevance
“…In terms of energy utilization, Guo et al (2012) reported that the ME as a percentage of energy intake was positively dependent on the dietary protein content. Positive correlation between specific dynamic action (SDA) and dietary protein levels was also found in some previous research (Chakraborty et al 1995;Gauquelin et al 2007). However, in this study, turtles fed 25-29% protein diets spend more ME compared with those fed 31-43% protein diets.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In terms of energy utilization, Guo et al (2012) reported that the ME as a percentage of energy intake was positively dependent on the dietary protein content. Positive correlation between specific dynamic action (SDA) and dietary protein levels was also found in some previous research (Chakraborty et al 1995;Gauquelin et al 2007). However, in this study, turtles fed 25-29% protein diets spend more ME compared with those fed 31-43% protein diets.…”
Section: Discussionsupporting
confidence: 81%
“…Nitrogen and energy budgets of animals give insights to protein metabolism and energy partitioning (Cui and Wootton ; Chakraborty et al ; Green and Hardy ; Guo et al ). From a nitrogen budget equation, we can identify the important features of protein utilization and metabolism and appraise the quality of feed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have shown that dietary protein aff ects SDA more than lipids and carbohydrates (Jobling and Davies, 1980;Tandler and Beamish, 1981;Zanotto et al, 1997). Some research has indicated a positive relationship between SDA and growth, showing that intensive SDA stimulates fast growth (Jobling, 1983;Brown and Cameron, 1991;Chakraborty et al, 1995;Carter and Hauler, 2000). In the present study, growth decreased with increased dietary protein.…”
Section: Suitable E/p For Growthsupporting
confidence: 48%
“…The present study showed a significant increase of juvenile A. astacus growth performance with a higher ration size in agreement with the results obtained by others authors (D'AGARO, 2004). CHAKRABORTY et al (1995) observed that the pattern of energy allocation of the common carp, Cyprinus carpio, varied with ration size. Increasing the ration level up to an optimal level, a larger amount of ingested energy is available to the crayfish for growth.…”
Section: Discussionmentioning
confidence: 96%